Assessment of Geotechnical Feasibility in Development of STIE BPD Semarang - Lisa Fitriyana (International Conference on Coastal and Delta Areas, 2017)
Geotechnical studies are an early stage for planning an infrastructure. In general, the geotechnical parameter value of a region is determined by soil characteristics. To know the condition of the soil layer under the structure, it is necessary geotechnical investigation. Toptografi uneven shape and the value of the low bearing capacity causes the need for planning the reinforcement. The reinforcement used is soil nailing and retaining wall. In this feasibility test used analysis of soil bearing capacity with plaxis program. The results of the analysis show that the reinforcement at the construction site of STIE BPD raises the value of its Savety Factor reaching 5.83.  Keywords: Geotechnical investigation, soils bearing capacity, reinforcement.